Pengaruh Bimbingan terhadap Mahasiswa tentang Manfaat Pemijatan Terhadap Tumbuh Kembang Bayi - Hilda Prajayanti (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Knowledge is the basis for a person in doing something, knowledge can be obtained from learning, experience and guidance. Based on the results of interviews from 9 students who attended the guidance, 7 students did not know the benefits of massage on infant growth and development and the management of Mom and Baby Spa. This service aims to determine the effect of guidance with student knowledge. The importance of providing education and guidance on the Benefits of Massage on Infant Growth and Management of Mom and Baby SPA to students is a preventive step. This activity begins with a pretest, counseling and posttest to determine the level of knowledge. The results obtained were an increase in knowledge of the Hopeful Midwifery Academy Students of Ibu Pekalongan after being given guidance on the benefits of massage on infant growth and development and management of Mom and Baby SPA.